Hybrid Active and Passive Control of Vibratory Power Flow in Flexible Isolation System - Y.P. Xiong; X.P. Wang; J.T. Xing; W.G. Price (Shock and Vibration)
A hybrid active and passive vibration control strategy is developed to reduce the total power flows from machines, subject to multiple excitations, to supporting flexible structures. The dynamic interactions between machines, controllers, and receiving structures are studied. A force feedback control process governed by a proportional control law is adopted to produce active control forces to cancel the transmitted forces in the mounts. Computational simulations of a simple and a multiple dimensional hybrid vibration isolation system are performed to study the force transmissibility and the total power flows from vibration sources through active and passive isolators to the supporting structures. The investigation focuses on the effects of a hybrid control approach to the reduction of power flow transmissions and the influence of the dynamic characteristics of the control on power flow spectra. The hybrid control mechanism is synthesised from the power flow analysis. Conclusions and control strategies, well supported by numerical simulations, are deduced providing very useful guidelines for hybrid vibration isolation design.